2021
DOI: 10.3389/fphys.2021.755060
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Sirtuin Biology and Nicotinamide Adenine Diphosphate Metabolism in Cardiovascular Disease—From Bench to Bedside

Abstract: Sirtuins (SIRT1–7) comprise a family of highly conserved deacetylases with distribution in different subcellular compartments. Sirtuins deacetylate target proteins depending on one common substrate, nicotinamide adenine diphosphate (NAD+), thus linking their activities to the status of cellular energy metabolism. Sirtuins had been linked to extending life span and confer beneficial effects in a wide array of immune-metabolic and cardiovascular diseases. SIRT1, SIRT3, and SIRT6 have been shown to provide protec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 127 publications
(155 reference statements)
1
11
0
Order By: Relevance
“…Therefore, the reduced oxidative stress and increased antioxidant activity induced by the mix of flavonoids presented in CCB could be mediated by the sirtuin pathway, as proven in in vitro and in vivo studies [ 38 , 46 , 47 , 49 ]. Interestingly, several studies have identified other sirtuins (mainly SIRT3 and SIRT6) to provide beneficial effects in cardiovascular diseases and energy metabolism [ 50 ]. Accordingly, a very recent report described the protective effect of the flavone acacetin against cardiac senescence via SIRT1-mediated activation of SIRT6/AMPK signalling pathway [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the reduced oxidative stress and increased antioxidant activity induced by the mix of flavonoids presented in CCB could be mediated by the sirtuin pathway, as proven in in vitro and in vivo studies [ 38 , 46 , 47 , 49 ]. Interestingly, several studies have identified other sirtuins (mainly SIRT3 and SIRT6) to provide beneficial effects in cardiovascular diseases and energy metabolism [ 50 ]. Accordingly, a very recent report described the protective effect of the flavone acacetin against cardiac senescence via SIRT1-mediated activation of SIRT6/AMPK signalling pathway [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…To clarify this hypothesis, it should be noted that elevated levels of NAD + positively upgrade the actions of sirtuins (SIRTs), which are specifically involved in cell survival and metabolic homeostasis ( 171 174 ). However, sirtuins are identified to be the NAD + -dependent type III deacetylases that may be collectively activated by increasing their co-substrate NAD + ( 173 ). This knowledge, in line with renalase’s capability to modulate the pool of NAD + , in the experimental setting, provides the proof of principle that renalase may be indirectly implicated in the modulation of sirtuin activities.…”
Section: The Regulatory Interplay Between Renalase and Sirtuins In Th...mentioning
confidence: 99%
“…This knowledge, in line with renalase’s capability to modulate the pool of NAD + , in the experimental setting, provides the proof of principle that renalase may be indirectly implicated in the modulation of sirtuin activities. This novel relationship may be of particular interest regarding the scope of this review, since there is ample current evidence that implies sirtuins significance in myocardial fibrotic response, and their cardioprotective effects in experimental settings ( 173 195 ). However, this is the first review that scrutinizes renalase’s activity through its relationship with sirtuins.…”
Section: The Regulatory Interplay Between Renalase and Sirtuins In Th...mentioning
confidence: 99%
See 2 more Smart Citations